1987
DOI: 10.1177/030098588702400105
|View full text |Cite
|
Sign up to set email alerts
|

Multifocal Retinitis in New Zealand Sheep Dogs

Abstract: Abstract. Thirty-nine percent of 1,448 working sheep dogs were affected with varying degrees of multifocal retinal disease on ophthalmoscopic examination. Lesions consisted of localized areas of hyperreflexia in the tapetal fundus, often associated with hyperpigmentation. Severely affected animals had widespread heperreflexia with retinal vascular attenuation. Only 6% of 125 New Zealand dogs raised in urban environment were similarly affected. Both eyes of 70 dogs from New Zealand were examined histologically.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
1

Year Published

1989
1989
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 12 publications
(1 reference statement)
2
29
1
Order By: Relevance
“…659,660 It has been suggested that OLM might be a problem in some dogs, such as working sheepdogs, 659 although clear data are lacking. Vomiting can occur from gastric irritation caused by larvae migrating through the gastric mucosa.…”
Section: Dogsmentioning
confidence: 99%
“…659,660 It has been suggested that OLM might be a problem in some dogs, such as working sheepdogs, 659 although clear data are lacking. Vomiting can occur from gastric irritation caused by larvae migrating through the gastric mucosa.…”
Section: Dogsmentioning
confidence: 99%
“…Such lesions have been observed in beagles diagnosed with acquired chorioretinitis . In working Border Collies and Borzois, it has been suggested that the retinopathy is due to microvascular accidents arising from athletic stress, while in New Zealand sheep dogs, it may be secondary to infectious causes . On the other hand, similar‐looking lesions may be of inherited origins.…”
Section: Introductionmentioning
confidence: 99%
“…4 In working Border Collies and Borzois, it has been suggested that the retinopathy is due to microvascular accidents arising from athletic stress, 5 while in New Zealand sheep dogs, it may be secondary to infectious causes. 6 On the other hand, similar-looking lesions may be of inherited origins. Hereditary retinopathy has been suspected in Czechoslovakian Wolfdogs 7 and Border Collies with focal or multifocal, irregular, small to large, hyper-reflective lesions with pigmented areas.…”
Section: Introductionmentioning
confidence: 99%
“…Ocular larva migrans is rare in dogs and results from aberrant hematogenous migration of Toxocara canis 1,2 . Most reports have documented intraocular larvae 2–5 . In an experimental study in the mouse, Ghafoor et al .…”
Section: Introductionmentioning
confidence: 99%
“…reported erratic migration of the parasite to the posterior pole of the eye 6 . Intraocular lesions caused by the larva in dogs include uveitis, vitreous alterations, retinal and optic nerve inflammation, and occasionally blindness 1,2,4 . Diagnosis of ocular larva migrans in dogs has been established through ophthalmoscopic and histopathologic observation of the larva, and by both immunofluorescence (ELISA) and immunohistochemistry.…”
Section: Introductionmentioning
confidence: 99%